Peran Dinas Sosial dalam penanganan lansia terlantar di Kota Padang - Septyla Dwi Putri; Rita Anggraini; Isnarmi Moeis; Al Rafni (Journal of Education, Cultural and Politics, 2026)
This study is motivated by the increasing issue of neglected elderly who require serious attention from the government, particularly throught the Social Service Office. The purpose of this study is to analyze the role of the Social Service of padang City in handling neglected elderly and to identify the in habiting factirs encountered. This research employs a qualitative approach with a descriptive method. Data collection techniques include interviews, observation, and documentation involving informants from the Social Service, community social workers, and the public. The results show that the Social Service has carried out multiple roles, including implementer, assessor, administrative facilitator, cross-sector coordinator, mediator, service provider, referral agent, social protector, and evaluator. However, these roles have not been fully optimized due to several obstacles such as the influx of elderly from outside regions, low family responsibility, low community awareness, budget constraints, internal conditions of the elderly, and socio-economic factors. Therefore, more proactive, integrated, and sustainable efforts are needed to improve the welfare of neglected elderly.